Characteristics of the magnetic energy recovery switch as a static Var compensator technology. Issue 8 (1st August 2015) - Cheng, Miao‐miao; Feng, Kai; Isobe, Takanori; Shimada, Ryuichi
Abstract : The magnetic energy recovery switch (MERS) has been proposed as a new reactive power compensator. It has been proven by some series compensation applications. In terms of shunt compensation, however, research on MERS is still at its early stage. In this study, the characteristics of MERS that operates as a static Var compensator (SVC‐MERS) technology are clarified. First, the operating principles of SVC‐MERS are described. The proposed device achieves continuously controllable capacitive power compensation with a simple control. Its unique characteristics include line frequency switching and wide‐range impedance control by a small capacitor, which lead to a wide operating range. Second, the electrical model of SVC‐MERS is described using analytical equations, and then followed by a detailed performance analysis. In particular, the optimal parameter design and the optimal combination of control variables are established from the perspectives of low peak capacitor voltage and current harmonics. Simulation and experimental results are presented to verify the characteristics of SVC‐MERS. Finally, SVC‐MERS is compared with other existing SVC technologies. In conclusion, SVC‐MERS is determined to be an attractive alternative shunt compensator.